Effectiveness of an institution-based adapted physical activity programme versus a home-based self-management programme for chronic poststroke adults: protocol for a randomised controlled study - Pascal Auquier; Etienne Satger; Nicolas Prieur-Blanc; Jean-Michel Viton; Laurent Bensoussan; Maëva Cotinat (BMJ Open)
Introduction Physical activity (PA) protects the cardiovascular system and reduces the risk of stroke recurrence. However, most stroke survivors have significantly lower daily PA levels than those recommended. Adapted PA programmes provide a useful means of increasing the daily PA levels of this population. PA programmes designed to encourage people walking have been found to be more effective than no intervention. Some programmes have been applied in institutional settings while others are done on an independent basis. The aim of this study will be to compare the two methods in terms of their impact on the daily walking rates of subjects with spastic hemiparesis following a chronic stroke. Secondary outcomes will include effects on walking ability, endurance, balance, quality of life and motivation for exercise.Methods and analysis This French single-centre randomised (1:1), controlled, two-arm, parallel, single-blind study will include 40 adults with chronic stroke spastic hemiparesis who are able to walk for 6 min. The primary outcome will be the participants’ daily activity measured via the number of steps performed per day using a Stepwatch device. We expect to establish that the institution-based programme will be more effective than a self-managed programme as a means of increasing the PA of chronic stroke subjects.Ethics and dissemination The protocol was approved by an independent National Ethics Committee (Comité de Protection des personnes Est IV). Participants will be asked to provide their signed informed consent prior to the study. The results will be disseminated via publications in the scientific literature, oral and poster presentations by partners at international scientific meetings and associations of patients.Trial registration NCT06061770.